GABAA receptor modulating steroid antagonists (GAMSA) are functional in vivo - Johansson, Maja; Strömberg, Jessica; Ragagnin, Gianna; Doverskog, Magnus; Bäckström, Torbjörn (The Journal of steroid biochemistry and molecular biology, 2016)
[Display omitted] •The neurosteroid allopregnanolone positively modulates the GABA-A receptor.•Allopregnanolone induces cognitive deficits and anesthesia.•Positive neurosteroid-enhancement of GABA-A receptors can be antagonized by GAMSA.•GAMSA blocks allopregnanolone-induced learning impairment and anesthesia in rats.•GAMSA blocks allopregnanolone-induced sedation and perturbed saccades in humans. GABAA receptor modulating steroid antagonists (GAMSA) selectively inhibit neurosteroid-mediated enhancement of GABA-evoked currents at the GABAA receptor. 3α-hydroxy-neurosteroids, notably allopregnanolone and tetrahydrodeoxycorticosterone (THDOC), potentiate GABAA receptor-mediated currents. On the contrary, various 3β-hydroxy-steroids antagonize this positive neurosteroid-mediated modulation. Importantly, GAMSAs are specific antagonists of the positive neurosteroid-modulation of the receptor and do not inhibit GABA-evoked currents. Allopregnanolone and THDOC have both negative and positive actions. Allopregnanolone can impair encoding/consolidation and retrieval of memories. Chronic administration of a physiological allopregnanolone concentration reduces cognition in mice models of Alzheimer’s disease. In humans an allopregnanolone challenge impairs episodic memory and in hepatic encephalopathy cognitive deficits are accompanied by increased brain ammonia and allopregnanolone. Hippocampal slices react in vitro to ammonia by allopregnanolone synthesis in CA1 neurons, which blocks long-term potentiation (LTP). Thus, allopregnanolone may impair learning and memory by interfering with hippocampal LTP. Contrary, pharmacological treatment with allopregnanolone can promote neurogenesis and positively influence learning and memory of trace eye-blink conditioning in mice. In rat the GAMSA UC1011 inhibits an allopregnanolone-induced learning impairment and the GAMSA GR3027 restores learning and motor coordination in rats with hepatic encephalopathy. In addition, the GAMSA isoallopregnanolone antagonizes allopregnanolone-induced anesthesia in rats, and in humans it antagonizes allopregnanolone-induced sedation and reductions in saccadic eye velocity. 17PA is also an effective GAMSA in vivo, as it antagonizes allopregnanolone-induced anesthesia and spinal analgesia in rats. In vitro the allopregnanolone/THDOC-increased GABA-mediated GABAA receptor activity is antagonized by isoallopregnanolone, UC1011, GR3027 and 17PA, while the effect of GABA itself is not affected.